The short run elasticity of National Health Service nurses' labour supply in Great Britain - Rowena Crawford; Richard Disney; Carl Emmerson (Institute for Fiscal Studies (IFS), 2015)
The paper investigates the short run responsiveness of National Health Service (NHS) nurses' labour supply to changes in wages of NHS nurses relative to wages in outside options available to nurses, utilising the panel data aspect of the Annual Survey of Hours and Earnings. We find the short run responsiveness of NHS nurses' labour supply to the relative wage of NHS nurses is positive and statistically significant, albeit economically small, in regions outside the London area. In contrast, in the London region, the short run elasticity is much higher. We discuss the policy implications of these findings.
Keywords: J31; J38; J45; 330; NHS; labour supply; relative wages